Yayoi Kusama in infinity - Laurberg, Marie; Holm, Michael Juul 1960-; Jørgensen, Lærke Rydal 1986- (Louisiana Museum of Modern Art, 2015)
Within a few years, Yayoi Kusama (born 1929) has become a favourite of Louisianas guests because of her Gleaming Lights of the Souls installation at the museum a mirror-lined room with hundreds of lamps in various colours that give the viewer a cosmic sensation of being in an infinite space. But with a career spanning six decades, Kusama is much more than this. She came onto the art scene almost as a woman counterpart to Andy Warhol in New York in the 1960s, where she expressed herself in a mixture of art, fashion and happenings. Since then, her striking visual language and constant artistic innovation have rightfully earned her a position as one of todays most prominent artists. Louisianas exhibition of Kusama tells the full story of this Japanese artist who with prodigious productivity has created an entire world unto itself, in which color, patterns and movement together bear witness to her fascination with the infinite. The Louisiana exhibition unfurls the whole of Kusamas lifes work: from early watercolours and pastels to her ground-breaking paintings and sculptures from the 1960s, psychedelic films, performances, installations and political happenings in the 1960s and the early 1970s, as well as shedding new light on works from the 1980s, after the artists return to Tokyo. Also on show exhibition are several of Kusamas recent installations, and a series of new paintnings by the 86-year-old Kusama, created especially for Louisianas exhibition. The exhibition is the first Kusama retrospective to take into account the artists interest in fashion and design but also includes several important works from her early period that have never before been exhibited. 00Exhibition: Louisiana Museum, Humlebaek, Denmark (17.9.2015 - 24.1.2016)